BARRIERS TO STUNTING PRIMORDIAL PREVENTION THROUGH PROSPECTIVE BRIDE’S ADVISORY SERVICE: A QUALITATIVE STUDY USING SOCIAL ECOLOGICAL MODEL - Wijaya, Made Indra; Komang Triyani Kartinawati; Luh Gede Pradnyawati; I Gusti Ngurah Made Bayuningrat; Tanjung Subrata; I Made Pariartha; A.A. Gede Indraningrat; Made Dharmesti Wijaya; Kartika Sari (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Since the Faculty of Medicine and Health Sciences, University of Warmadewa, launched community-oriented medical education (COME), the stunting prevalence in Gianyar Residence decreased from 12.1% (2018) to 11.1% (2019). In 2021, it decreased to 5.1% which was lower than Bali province (10.9% in 2021) and much less than the Republic of Indonesia (24.4%). The PentaCOME (Pentahelix Community-Based Medical Education) project, the modification of COME, was the collaboration of the Indonesian Ministry of Education, Culture, Research, and Higher Education, the Warmadewa University, as well as PT. Sido Muncul is implemented to further lower stunting prevalence via the “Stunting Primordial Prevention Through Prospective Brides Advisory Service” initiative in Payangan District. The present study was intended to figure out barriers to implementing such initiatives. This is a qualitative study using in-depth interviews and focus group discussions (FGDs) in obtaining data. Purposive sampling was used to select informants who represented academicians (3), businessmen (2), community (9), government (3), and media (3) (i.e., Penta helix components). Twenty in-depth interviews and two FGDs involving academician, community, government, and media were conducted during the 1 September 2022 – 15 October 2022 period. Two coders transcribed and coded independently. The social-ecological model was used to categorize the codes. Informants described that they never heard about the ELSIMIL application (ELSIMIL stands for Electronic Siap Nikah dan Hamil which means ‘prepared to get married and pregnant application’) at the personal level. The “No pregnancy, no marriage” motto (i.e., social pressure to get pregnant before marriage among Balinese) was found a barrier at the interpersonal level. At the institutional level, key informants stated the prospective bride’s advisory service and ELSIMIL application campaign were not adequate. At the community level, the family support team community has been established, however, they could not fulfill their function properly due to the “no pregnancy, no marriage” motto. At the policy level, the traditional village assembly (i.e., “Majelis Desa Adat”) has not issued regulations regarding the prospective bride’s advisory service.  A lack of cross-sector collaboration was also reported as a barrier to this initiative. A well-planned promotion could socialize ELSIMIL application among prospective brides. Advocacy to the traditional village assembly might diminish the “no pregnancy, no marriage” motto. Pentahelix collaboration needs to be established to achieve the “zero stunting for golden generation” goal.